Youth Participation in Climate Change Movements: A Sociopolitical Perspective on Environmental Activism in Indonesia - Risaldi, Ahmad; Ramadani, Abdul Muin (Moccasin Journal De Public Perspective, 2025)
Youth participation in climate change movements is increasingly vital in addressing environmental challenges, especially in vulnerable countries like Indonesia. This study explores youth engagement in climate activism from a sociopolitical perspective, focusing on motivations, strategies, and structural factors influencing participation. Using a qualitative approach, data were gathered through interviews, focus groups, and observations with young activists from diverse backgrounds. Findings show that personal experiences with environmental risks, moral responsibility, and social awareness drive activism. Sociopolitical elements such as access to resources, institutional backing, and government policies can either support or hinder involvement. Youth activists combine digital advocacy with community-based initiatives to amplify impact and reach varied audiences. The study highlights how individual agency, networks, and structural contexts interact to shape activism’s effectiveness. By examining these dynamics, the research provides insights into the motivations and challenges faced by young activists and offers recommendations for policymakers, educators, and organizations to strengthen youth engagement through inclusive and supportive strategies.